PROGRAM PENDAMPINGAN: DETEKSI TUMBUH KEMBANG, GAYA BELAJAR, DAN POLA ASUH ORANGTUA - Marsidi, Sitti Rahmah; Dewanti, Lintang Purwara; Harlianty, Rully Afrita (Universitas Mataram, 2024)
The preschool period is the optimal period for children to show their interest and development in language, social interaction, and environmental exploration. It is important to recognize children's development and growth to optimize their potential, character and growth and development. This community service is carried out to facilitate schools and parents to better understand the condition of their students and children. This activity is also a preventive measure for children's development and growth problems. The method of this activity is in the form of a mentoring program, namely assessment and education about children's growth and development, children's learning styles, and parenting patterns, consultations, as well as providing guidance on detecting children's growth and development and psychology to schools. Activities were carried out on May 11, July 6, July 13, and July 30 2024. The measurement results showed that most children had the average intelligence category (63.64%), most of the children's development and growth measurements were in the normal category, namely as many as 21 children (63.64%), the highest nutritional status was normal nutritional status, 26 children (78.79%), and the visual learning style that most students had, namely 17 children (51.52%). All types of parenting styles are democratic. Regarding the effectiveness of education, it shows that there is no significant difference in results (t= -0.977; p= >0.05). This means that providing education has no influence on parents' knowledge regarding physical development, psychological development and parenting styles. The conclusion of this mentoring activity is that it is able to facilitate the school and parents to recognize the condition of students and children. However, regarding the objectives of the mentoring process, it can be said that it has not been successful due to several weak factors in this activity, such as many educational participants not attending, and some assessment data not being identified. Key words: growth and development, learning styles, parenting patterns